2014
DOI: 10.1007/s40477-014-0130-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of emergency physician performed graded compression ultrasound study in acute appendicitis: a prospective study

Abstract: Purpose Accurate early diagnosis of appendicitis can decrease its complications and minimize the mortality, morbidity and costs. This prospective study evaluates the accuracy of bedside emergency physician performed ultrasound study diagnosis in acute appendicitis. Methods Patients who were suspicious to have appendicitis based on their clinical findings were included and underwent emergency physician performed ultrasound study. Then they were followed up until the recognition of final diagnosis based on patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…While ultrasound is a safe and generally effective imaging modality, its utility is limited because it is highly operator‐dependent and has limited sensitivity and specificity for the diagnosis of appendicitis, particularly outside of the pediatric population . Emergency physician‐performed ultrasound has been reported to have sensitivity 44–67%, specificity 85–98%, and accuracy 67%, although this specifically relates to clinicians with limited training in sonography . However, one study reports that even formal ultrasound performed by medical sonographers was unable to visualize the appendix in 45% of cases, yielding sensitivity 51.8% and specificity 81.4% .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While ultrasound is a safe and generally effective imaging modality, its utility is limited because it is highly operator‐dependent and has limited sensitivity and specificity for the diagnosis of appendicitis, particularly outside of the pediatric population . Emergency physician‐performed ultrasound has been reported to have sensitivity 44–67%, specificity 85–98%, and accuracy 67%, although this specifically relates to clinicians with limited training in sonography . However, one study reports that even formal ultrasound performed by medical sonographers was unable to visualize the appendix in 45% of cases, yielding sensitivity 51.8% and specificity 81.4% .…”
mentioning
confidence: 99%
“…6 Emergency physician-performed ultrasound has been reported to have sensitivity 44-67%, specificity 85-98%, and accuracy 67%, although this specifically relates to clinicians with limited training in sonography. 7,8 However, one study reports that even formal ultrasound performed by medical sonographers was unable to visualize the appendix in 45% of cases, yielding sensitivity 51.8% and specificity 81.4%. 9 Further, although the test accuracy of ultrasound in the case of pediatric abdominal pain concerning appendicitis has long been viewed as superior to that of adults, the sensitivity of ultrasound has been reported to be as low as 35% in centers that do not use the technology often.…”
mentioning
confidence: 99%
“…Although this was a well‐designed study with a well‐structured training program, the POCUS performers were inexperienced physicians in terms of using bedside US and sample size of the study was small. In another study, Fathi et al . found a sensitivity and specificity of 44.18 and 85.18%, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…This study shows that focused right lower quadrant US performed by EPs is highly sensitive and specific in the diagnosis of AA, and POCUS, with clinically important EPs’ clinical decision making. Previous studies reported the sensitivity and the specificity of bedside US performed by EPs in the diagnosis of AA as being between 39 to 96.4 and 67.3% to 98.4%, respectively . In a study combining POCUS and scoring systems, the sensitivity and specificity of POCUS for the diagnosis of AA were 73.3 and 67.3%, respectively .…”
Section: Discussionmentioning
confidence: 96%
“…[ 21 ] Another study assessed the ultrasound diagnostic accuracy with graduated compression techniques in emergency situation at the patient's bed, but its sensitivity was low and was recommended to be combined with clinical and laboratory findings. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%